Bellactis lux n. sp. (Cnidaria: Anthozoa: Actiniaria: Aiptasiidae), a new sea anemone from the Gulf of Mexico - Delgado, Alonso; Larson, Paul; Sheridan, Nancy; Daly, Marymegan (Zootaxa, 2023)
Here we describe a new species of sea anemone from the family Aiptasiidae based on specimens collected from the Gulf of Mexico (USA: Florida & Alabama). Accounts of this species have been known since the early 1990’s, primarily from an underwater field guide and hobbyist aquarium literature under the name “Lightbulb Anemone.” We describe it as a new species from the genus Bellactis based on anatomy, histology, and cnidom. Members of this species are small in size, with a smooth, typically contracted column divided into regions based on color and bearing rows of two or three elevated cinclides in the mid column. Their tentacles are distinctive, translucent, distally inflated and can be bulbous in shape, with sub annular rings. This description synthesizes information about Bellactis and contextualizes what is known about its diversity in light of other members of the Aiptasiidae.